Development of a Grain-and-Legume-Based Snack with Amaranth, Quinoa and Chia Seeds - Silvia Farah; Jannika Bailey; Pablo Mezzatesta; Emilia Raimondo (Biology and Life Sciences Forum, 2023)
Globally, 1 in 2 people want to consume more plant-based foods, so developing nutritionally balanced foods for this area is a response to a growing need of the population. The objective was to develop snack alternatives with amaranth, quinoa and chia seeds, supplemented with protein. For this purpose, three mixtures were prepared, the first of rice flour with lentil flour (M1), another of rice flour with pea flour (M2) and another of wheat flour with chickpea flour (M3). The same amount of amaranth, quinoa and chia seeds were added to all three. The same proportion of the rest of the ingredients was used, varying only the seasonings. The cooking time was 10 min at 180 °C in all cases. The preparations were carried out in triplicate and analyses in duplicate. Once prepared, protein, total fat, ash, moisture and fiber were determined using official analytical techniques, carbohydrates using difference, energy value using calculations and fatty acid profile using gas chromatography. For statistical analysis, the Tukey test was applied. The highest protein value was 15.84 ± 0.34 g% (M1). The highest lipid value was 21.44 ± 0.13 g% (M3), providing omega 9, 3 and 6 fatty acids and, to a much lesser extent, saturated fatty acid. All options have a good contribution of dietary fiber: 7.39 ± 0.14 g% (M1); 7.71 ± 0.09 g% (M2) and 7.55 ± 0.23 g% (M3). The acceptability was above 94% in all cases. It was possible to formulate healthy snacks suitable for vegetarians.